Краткий музыкальный словарь для учащихся - Булучевский Юрий Степанович (Просвещение, 1989)
Экземпляры: БС (20170302) / Инвентарный номер: РТШ48049 / Цена: 1.40 / Сис.шифр: 85.31я2 / Авт.знак: Б 90 / ГРНТИ: 18.41 / ББК: 85.31я2